2011
DOI: 10.1364/oe.19.021258
|View full text |Cite
|
Sign up to set email alerts
|

Motion correction for phase-resolved dynamic optical coherence tomography imaging of rodent cerebral cortex

Abstract: Cardiac and respiratory motions in animals are the primary source of image quality degradation in dynamic imaging studies, especially when using phase-resolved imaging modalities such as spectral-domain optical coherence tomography (SD-OCT), whose phase signal is very sensitive to movements of the sample. This study demonstrates a method with which to compensate for motion artifacts in dynamic SD-OCT imaging of the rodent cerebral cortex. We observed that respiratory and cardiac motions mainly caused, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 19 publications
2
87
0
Order By: Relevance
“…16 We used a large-bandwidth near infrared light source (1310±170 nm) for a large imaging depth (1 mm) and high axial resolution (3.5 mm in tissue). The light source with the center wavelength of 1300 nm was used as it offers a larger imaging depth than conventional 800-nm light sources.…”
Section: Spectral-domain-optical Coherence Tomography System and Scanmentioning
confidence: 99%
See 1 more Smart Citation
“…16 We used a large-bandwidth near infrared light source (1310±170 nm) for a large imaging depth (1 mm) and high axial resolution (3.5 mm in tissue). The light source with the center wavelength of 1300 nm was used as it offers a larger imaging depth than conventional 800-nm light sources.…”
Section: Spectral-domain-optical Coherence Tomography System and Scanmentioning
confidence: 99%
“…An angiogram was obtained using the method described previously. [16][17][18] Dynamic Light Scattering-Optical Coherence Tomography Analysis Technical details of DLS-OCT theory and analysis have been described in our previous publication. 19 In brief, dynamic OCT imaging of a sample produced four-dimensional (space and time) data of the complex-valued reflectivity, R(r, t).…”
Section: Spectral-domain-optical Coherence Tomography System and Scanmentioning
confidence: 99%
“…As the oversampling decreases (dy/ω 0 increases), the RMS error increases. Here, as previously used in [19], ω 0 is the 1/e radius of the diffraction-limited spot size at the Gaussian beam focus. The RMS error was compared to a Monte Carlo simulation.…”
Section: Motion Correction Performancementioning
confidence: 99%
“…Previous work typically required either stable data at the time of imaging [17,18], or a phase reference was used, such as a coverslip placed on the sample or tissue, to compensate for optical path length fluctuations [14]. Additionally, other efforts have shown that motion could be corrected by using only the acquired OCT data for numerical defocus correction and other phase-resolved techniques [19,20]. Most of these techniques, though, are restricted to one-or two-dimensional motion correction.…”
Section: Introductionmentioning
confidence: 99%
“…Methods that iteratively maximize cross-correlation of successive B-scans prior to OCTA processing have been used to estimate displacement and compensate bulk image shifts as well as global phase variations in the axial and lateral directions [34][35][36]. However, the actual three-dimensional nature of eye motion during scanning challenges this approach, which is limited to in-plane shifts.…”
Section: Introductionmentioning
confidence: 99%